Development of an in situ gel containing tinidazole-loaded polymeric nanoparticles for oral cavity administration - Ho, Hoang Nhan; Phan, Thi Thao Ngoc (Tạp chí Y Dược Huế, 2025)
Background: Tinidazole (TNZ) demonstrates greater efficacy against anaerobic bacteria, particularly Gram-negative strains, compared to metronidazole. Nanosizing TNZ and incorporating it into in situ gel formulations for topical periodontitis treatment offers several advantages. Objectives: This study aimed to formulate an in situ gel containing preformed Eudragit RSPO-based nanoparticles (NPs) of TNZ and to evaluate its physicochemical properties. Materials and methods: Poloxamer 407 was used as a thermosensitive gelling agent, either alone or in combination with other gelling agents. The in situ gels containing TNZ NPs were prepared and evaluated for physicochemical properties. Results: The in situ gel containing TNZ NPs, formulated with Poloxamer 407 and sodium alginate, exhibited a smooth texture, a gelation temperature of 31.33 ± 0.24 °C, a gelation time of less than one minute, a pH of 6.72 ± 0.03, and a stable gel state over an extended period. Compared to the in situ gel with TNZ material, the TNZ NP-loaded gel prolonged drug release. The drug release mechanism was best described by the Higuchi model (with F0). Conclusion: This TNZ NP-loaded in situ gel formulation shows promise for further research in periodontitis treatment.